Comparable survival benefit of local excision versus radical resection for 10- to 20-mm rectal neuroendocrine tumors. Issue 4 (April 2022) - Chen, Qichen; Chen, Jinghua; Huang, Zhen; Zhao, Hong; Cai, Jianqiang
Abstract: Objective: The optimal surgical management for 10- to 20-mm rectal neuroendocrine tumors (RNET) is still a matter of debate. This study aimed to explore the optimal surgical approach for 10- to 20-mm RNET by comparing the outcomes between local excision and radical resection. Method: We extracted clinicopathological information of 10- to 20-mm RNET from the Surveillance, Epidemiology, and End Results (SEER) database. The 1:2 propensity score matching (PSM) method was used to balance the imbalanced baseline covariates ( P  < 0.05) between the local excision group and radical resection group. A Cox proportional hazards model was used to identify the risk factors associated with cancer-specific survival (CSS) and overall survival (OS). Result: A total of 531 RNET patients 10–20 mm in size were included. Patients receiving radical resection had larger tumor sizes ( P  < 0.001), higher T stages ( P  < 0.001), higher N stages ( P  < 0.001), higher M stages ( P = 0.002) and higher grades ( P  = 0.041). For 10–20 mm RNET patients, radical resection had no survival benefit compared with local excision (CSS: HR = 2.048, 95% CI 0.553–7.576, P  = 0.283; OS: HR = 1.090, 95% CI 0.535–2.219, P  = 0.813). After 1:2 PSM, there was no significant difference between local excision and radical resection. Radical resection still had no survival benefit over local excision (CSS: HR = 0.449, 95% CI 0.050–4.022, P  = 0.474; OS: HR = 1.408, 95% CI 0.488–4.061, P  = 0.527). In a multivariate analysis of CSS, age > 60 years old ( P = 0.005), tumour size 14–20 mm ( P = 0.011) and M1 stage ( P  < 0.001) were identified as independent prognostic factors for worse CSS. In multivariate analysis of OS, age>60 years ( P ＜0.001), male sex ( P = 0.007), black race ( P = 0.016), and T2/T3/T4 stage ( P = 0.007) were significantly associated with worse OS. N stage was not an independent predictive factor for CSS and OS. Conclusion: This study revealed that for 10- to 20-mm RNET patients, there was no survival benefit for radical resection compared with local excision, which suggested that local excision may be an adequate treatment for these patients.